Young people's priorities for the self‐management of distress after stoma surgery due to inflammatory bowel disease: A consensus study using online nominal group technique - Benjamin Saunders; Kay Polidano; Lucy Bray; Tamsin Fisher; Nadia Corp; Megan McDermott‐Hughes; Adam D. Farmer; Beth Morris; Sahara Fleetwood‐Beresford; Carolyn A. Chew‐Graham (Wiley, 2024)
Abstract Introduction The aim of this study was to gain consensus among young people with a stoma due to inflammatory bowel disease (IBD) on the priorities for the content of an intervention for the self‐management of stoma‐related distress. The current identification and management of distress in young people with a stoma is often suboptimal in clinical settings and there is a need for improved support resources. Methods Two consensus group meetings were carried out via online video conferencing, using nominal group technique. Participants generated, rated on a Likert scale and discussed, topics for inclusion in a future self‐management intervention. Results Nineteen young people, aged 19-33, with a stoma due to IBD took part in one of two group meetings. Participants were located across England, Scotland, and Northern Ireland. Twenty‐nine topics were generated by participants, seven of which reached consensus of ≥80%, that is, a mean of ≥5.6 on a 7‐point Likert scale. These were: receiving advice from young people with lived experience of stoma surgery; advice on/addressing concerns about romantic relationships, sex and intimacy; information about fertility and pregnancy related to stoma surgery; stoma 'hacks', for example, useful everyday tips regarding clothing, making bag changes easier and so forth; reflecting on and recognising own emotional response to surgery; tips on managing the stoma during the night; and processing trauma related to the illness and surgery journey. Conclusions Findings extend previous research on young people's experiences of stoma surgery, by generating consensus on young people's priorities for managing distress related to surgery and living with a stoma. These priorities include topics not previously reported in the literature, including the need for information about fertility and pregnancy. Findings will inform the development of a self‐management resource for young people with an IBD stoma and have relevance for the clinical management of stoma‐related distress in this population. Patient or Public Contribution Three patient contributors are co‐authors on this paper, having contributed to the study design, interpretation of results and writing of the manuscript. The study's Patient and Public Involvement and Engagement advisory group also had an integral role in the study. They met with the research team for four 2‐h virtual meetings, giving input on the aims and purpose of the study, recruitment methods, and interpretation of findings. The group also advised on the age range for participants. The views of young people with a stoma are the central component of the study reported in this paper, which aims to gain consensus among young people with an IBD stoma on their priorities for the content of a resource to self‐manage distress related to stoma surgery.